2019
DOI: 10.1016/j.socec.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of the disposition effect: Who and when?

Abstract: The disposition effect (DE) is a common bias by which investors tend to sell winning assets too soon and hold losing assets too long. We complement the existing evidence in three directions. First, we check whether the DE is robust to realistic features such as transaction costs and competitive payment schemes. Second, by using a gender-balanced design, we check for gender differences. Third, we search for psychological correlates of the DE. We find that the DE is positive and significant in all our treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 74 publications
(108 reference statements)
0
8
0
3
Order By: Relevance
“…Chui found that belief in mean reversion does not affect the disposition effect and observed that internal locus of control has morepronounced disposition effects. Subsequently, studies established the relationship between the disposition effect and investors' characteristics such as gender (Da Costa et al 2008;Rau 2015;Braga and Fávero 2017;Cueva et al 2019), experience (Dhar and Zhu 2006;Da Costa et al 2013), and various activities and interventions (Bulipopova et al 2014;Rau 2015;Cao et al 2022). The investigations above into the disposition effect have primarily focused on countries like the United States, Europe, and parts of Asia-particularly China.…”
Section: Disposition Effectmentioning
confidence: 99%
“…Chui found that belief in mean reversion does not affect the disposition effect and observed that internal locus of control has morepronounced disposition effects. Subsequently, studies established the relationship between the disposition effect and investors' characteristics such as gender (Da Costa et al 2008;Rau 2015;Braga and Fávero 2017;Cueva et al 2019), experience (Dhar and Zhu 2006;Da Costa et al 2013), and various activities and interventions (Bulipopova et al 2014;Rau 2015;Cao et al 2022). The investigations above into the disposition effect have primarily focused on countries like the United States, Europe, and parts of Asia-particularly China.…”
Section: Disposition Effectmentioning
confidence: 99%
“…This task has been widely used in the study of the disposition effect, another well-known bias in behavioral finance. We use the data collected in this experiment to investigate the disposition effect in a separate paper (Cueva et al 2018).…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…Among the various measures collected, we primarily focus on risk aversion and financial literacy, since these are most likely to have a chance of explaining some portion of the gender gap in trade volume a priori. The other psychological measures include a short version of the Big Five test and some items aimed at exploring the sources of the disposition effect, investigated in a separate study (Cueva et al 2018). 5 These variables are used as additional controls in the last part of our analysis (see Appendix C for details).…”
Section: Following Weber and Welfensmentioning
confidence: 99%
“…This outcome was also found for the cutting gains bias. Finally, according to Cueva et al (2019), disposition effect and cutting gains scores are negatively related to experience.…”
mentioning
confidence: 92%